The utilization of APACHE II score to predict the incidence of ventilator-associated pneumonia in patients with severe traumatic brain injury: A single-center study - Agung Budi Sutiono; Muhammad Zafrullah Arifin; Hadian Adhipratama; Yulius Hermanto (Interdisciplinary Neurosurgery, 2022)
Background: The presence of pneumonia in patients with traumatic brain injury (TBI) is associated with high fatality and poor outcomes. Patients with severe TBI are often admitted to the intensive care unit, in which the utilization of APACHE II score is commonly used to predict mortality risk. Therefore, we aimed to evaluate the association between the APACHE II score and the incidence of ventilator-associated pneumonia (VAP) in patients with severe TBI. Methods: This was a retrospective study. A total of 32 patients with severe TBI who were admitted to the intensive care unit at Dr. Hasan Sadikin Hospital from January 1, 2018 – December 31, 2019, were investigated in this study. The patients were assessed for APACHE II score within 24 h of admission and the occurrence of VAP. Results: To define the risk of having VAP in patients with severe TBI, we analyzed APACHE II score using ROC analysis. We identified that a value of 15 as a cut-off for the APACHE II score for predicting VAP occurrence in patients with severe TBI (p = 0.0307). Then, we evaluated the reliability of the APACHE II score as a predictor of VAP occurrence compared to the duration of mechanical ventilation and tracheostomy. In subsequent analysis, high APACHE II score (OR = 10.20 (1.21–229.90), p = 0.0385) and prolonged mechanical ventilation (OR = 27.59 (2.27–1149.00), p = 0.0067) were associated with a higher chance of having VAP during the period of hospitalization. Conclusion: Patients with severe TBI with a high APACHE score (≥15) or prolonged mechanical ventilation (15 days) are at higher risk for having VAP during the period of hospitalization.